Pembinaan Warga Gereja Menurut Kitab Matius - Andar G, Pasaribu; Geby N Sinaga; Naomi Butar-Butar; Anabella Pashya (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
Church Community Development is a church activity that aims to mature the faith of church members, and by carrying out this activity it is hoped that the congregation's faith will experience growth towards maturity in life as believers. The formation of church members based on the Book of Matthew explores the principles of Christian life contained in the depths of the Gospel. The focus includes understanding the teachings of Jesus, developing spirituality, and applying spiritual values ​​in everyday life. Through in-depth reflection on the teachings of the Book of Matthew, this training aims to strengthen the faith and shape the character of church members so that they become enlighteners in society and are able to have a positive impact on the surrounding environment.